Long-Term Sensitization Training Produces Spike Narrowing in Aplysia Sensory Neurons - Antzoulatos, Evangelos G. (J Neurosci, 2007)
Both short- and long-term sensitization of withdrawal reflexes of Aplysia are attributable at least in part to facilitation of the sensorimotor synapse. Previously, short-term synaptic facilitation has been associated with spike broadening and no change in temporal dynamics of burst transmission. In the present study, we examined whether long-term sensitization (LTS) is also associated with spike broadening and whether long-term synaptic facilitation is accompanied by changes in temporal dynamics. The results indicate that the temporal dynamics of the sensorimotor synapse are preserved after long-term facilitation. However, in contrast to short-term sensitization, LTS was accompanied by spike narrowing. The spike narrowing was observed both in centrally triggered spikes in isolated ganglia and in peripherally triggered spikes in reduced tail preparations. In addition, in reduced tail preparations, fewer spike failures in the afferent discharge of sensory neurons occurred in response to tail stimulation after ipsilateral LTS. Collectively, the results reveal that long-term sensitization affects the spike waveform of sensory neurons and enhances the sensory neuron responses to peripheral stimuli, but does not modify the synaptic dynamics of homosynaptic depression.